농산물 브랜드 가치 분석 : 농협 하나로 클럽 축산물 브랜드를 중심으로 - 황윤재 (한국농촌경제연구원, 2007)
The number of agricultural product brands has been increasing largely every year. As of 2006, the number of agricultural product brands has increased by 39.4% compared to the number in 2000. There were 6,552 agricultural product brands in 2006. The number of registered agricultural product brands also increased. However, the brand registration rate is still low despite improvement. The registration rate of stock farm products is higher than that of other agricultural products. Even though the number of stock farm products with brands is relatively large, stock farm products with brands account for less than 50% of all stock farm products in most breeds. Among all stock farm products, the number of pork brands is larger than the number of any other breed. Currently, many agricultural product brands including stock farm product brands are not achieving the main purposes of differentiating the branded products and creating added value for the producer. This study analyzed the brand assets of stock farm products; the main components of the brand assets are brand awareness, brand image, brand loyalty, quality perception, and consumers' market behavior. The brands that were surveyed for this study are main brands which are sold at Nonghyup Hanaro Club in Yangjae Dong. The purposes of this study were to understand the actual conditions and problems of agricultural product brands, to assess individual brand assets, and to provide useful information for establishing improvement plans and marketing strategies. The study found that there are correlations among the components of brand assets; a leading brand has not only a highest total assessment index but also highest assessment indexes in classified brand asset components in general. The differences of brand asset assessment between a leading brand and other brands are relatively large in chicken and pork but relatively small in beef. There were limitations in forming niche markets for some chicken brands due to their low brand awareness. Although most pork brands included in the study have pretty large market shares in the national pork market, their brand assets assessed by consumers were low. The study shows that a brand could have a relatively high brand asset despite its low brand awareness compared to a leading brand due to a successful marketing strategy of product differentiation. Only two beef brands were surveyed for the study and these brands are the only brands currently sold at the Hanaro Club. The study showed that the differences of brand assets between the two brands are not so huge compared to the cases of chicken and pork. The study points out that an effective individual strategy for quality or image differentiation is needed for an individual stock farm product brand to achieve its original purposes of product differentiation and a higher value. Researchers: Yun-Jae Hwang E-mail address: yjhwang@krei.re.kr